Study on Efem Cukuru Gold Ore Deposit and Recovery of Gold by Flotation - Sen, S.; Tanriverdi, M.; Cicek, T.; Oyman, T.; Cilingir, Y. (Asian Journal of Chemistry, 2010)
This study reports the information about Efem cukuru gold ore deposit and the results of the flotation experiments. Classical first-order kinetic flotation model was used for the evaluation of the experimental data, recovery and flotation rate constants describing the flotation timerecovery profiles for different reagent combinations.